BSCI-03. T CELL EXHAUSTION SIGNATURES VARY BY TUMOR TYPE AND ARE INDEPENDENT OF INTRACRANIAL LOCATION. (12th August 2019) - Woroniecka, Karolina; Chongsathidkiet, Pakawat; Cui, Xiuyu; Dechant, Cosette; Wilkinson, Daniel; Fecci, Peter
Abstract: T-cell exhaustion is a hindrance to the efficacy of immune checkpoint blockade. This study is among the first to examine, and credential as bona fide, exhaustion among T cells infiltrating murine models of brain metastasis, including breast, lung, and melanoma cancers. Furthermore, this study demonstrates the utility of a 4-1BB agonist antibody in certain tumors resistant to PD-1 blockade alone. METHODS: Tumor-infiltrating and peripheral blood lymphocytes (TILs and PBLs) were isolated from intracranial and subcutaneous immunocompetent murine models of glioma, breast, lung, and melanoma cancers. Levels of exhaustion-associated inhibitory receptors and post-stimulation levels of the cytokines IFNγ, TNFα, and IL2 were assessed by flow cytometry. Anti-PD-1 and anti-4-1BB monoclonal antibodies were utilized as a therapeutic exhaustion-countering strategy and median survival was assessed. RESULTS: Our data reveal that tumors, regardless of their intracranial or subcutaneous location, elicit unique T-cell exhaustion signatures among infiltrating T cells characterized by: (1) prominent upregulation of multiple immune checkpoints; (2) stereotyped T-cell transcriptional programs matching classical virus-induced exhaustion; and (3) notable T-cell hyporesponsiveness in tumor-specific T cells. Exhaustion signatures differ predictably with tumor identity, but remain stable across manipulated tumor locations. Anti-PD-1 monoclonal antibody alone did not improve median survival in any tumor type tested. In tumors with high levels of 4-1BB expression, anti-4-1BB and anti-PD-1 therapy resulted in improvement in median survival. CONCLUSIONS: Distinct cancers possess similarly distinct mechanisms for exhausting T cells. Each tumor type demonstrated a unique T cell exhaustion signature regardless of location. 4-1BB may serve as a therapeutic adjunct to anti-PD-1 monoclonal therapy in tumors which may be resistant to PD-1 blockade alone.